Music Therapy in Enhancing Learning Attention of Children with Intellectual Disability - Dada, Akintunde Oluseyi; Adeleke, Owoade Philip; Aderibigbe, Samson Akinwumi; Adefemi, Michael Adeife; Apie, Martina Ayibeya (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Inattention is one of the significant problems that inhibit learning among children with intellectual disabilities. However, several strategies and therapies have been developed to solve the problem. This study, therefore, investigates the effectiveness of music therapy in enhancing attention among children with intellectual disability. A pretest-posttest control experimental research design was adopted. The experiment was carried out for six weeks using Music Therapy Treatment Package on 24 children with intellectual disability that were randomly selected Modupe Cole Momerial Childcare and Treatment Home/School, Akoka, Yaba, Lagos. A validated Attention Observation Rating Scale (AORS) with a reliability coefficient of 0.88 was used for this study. Three hypotheses were tested in the study, and Analysis of Covariance (ANCOVA) was used for data analysis. This study revealed that music therapy is effective in enhancing attention among children with intellectual disabilities. Sex and level of severity of the disability were also tested as moderator variables, but they have no significant main or interaction effect with music therapy in enhancing attention for children with intellectual disability. The finding is that music therapy is significantly effective in enhancing attention for children with intellectual disability regardless of their sex or level of severity. It was concluded that attention deficit could be improved for children with intellectual disability. Therefore, Music therapy was recommended for use in the school with adequate teacher training.